The influence of metabolic syndrome on the development and clinical manifestations of benign prostatic hyperplasia - V. B. Filimonov; R. V. Vasin; A. A. Kostin; V. N. Panchenko (Исследования и практика в медицине, 2018)
Benign prostatic hyperplasia (BPH) — one of the most common urological diseases that lead to the development of symptoms of the lower urinary tract (SLUT). BPH-multifactorial disease, in which a significant role is given to increase the activity of the enzyme 5a-reductase and hormonal imbalance associated with the exchange of testosterone and dihydrotestosterone. However, to date, not all aspects of the etiology and pathogenesis of this condition have been studied. The results of numerous studies indicate a significant role of complex metabolic disorders included in the modern concept of "metabolic syndrome" (MS), the development and progression of BPH/SLUT. The main pathogenetic factors leading to the formation of BPH and concomitant urination disorders are considered to be a violation of the balance of sex hormones, the development of chronic ischemia of the pelvic organs, a violation of carbohydrate and lipid metabolism. The relationship between BPH and MS is one of the most urgent problems of modern medicine. Different components of MS independently from each other can influence more pronounced progression of BPH/SLUT in comparison with development of this disease in men without metabolic disorders that is the reason of lower efficiency of surgical and medical treatment of this group of patients.